ANALISIS CUTI HAID PADA PEKERJA PEREMPUAN DI PT X BERDASARKAN UNDANG-UNDANG KETENAGAKERJAAN NO. 13 TAHUN 2003 - ANN Bella Yoselina Jingga Savitri (2023)
Women will experience biological phases such as menstruation every month. During menstruation normally women will feel pain. In the Labor Law No. 13 of 2003, every female worker who feels pain during menstruation can get menstruation leave, but not all companies implemented the right to menstruation leave for their workers. This research was conducted to analyze menstruation leave at PT X with female workers based on Labor Law No. 13 of 2003. This research is a qualitative research. Qualitative research was chosen so information related to the implementation of menstruation leave for female workers can be explored in depth. There were five informants consisting of HRD and female workers. The results of the study are the company never implemented menstrual leave. If a worker feels pain during menstruation, it included in the sick leave and will be deductions from the accommodation fee. Based on the results concluded that the company has not implemented menstrual leave because there are no indicators that guarantee workers not abuse the rights. Suggestions that can be given are use menstrual cycle tracker applications and the procurement of health workers in companies so it easier to record and abuse of rights can be avoided.